PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN HOTEL PATRA JASA SEMARANG - Tiara Jovita Sirait; Apriatni EP (Universitas Diponegoro, 2017)
This research is motivated by the increasing of competition among the competitors of hospitality service company. There are several complaints from Hotel Patra Jasa Semarang employees regarding organizational culture, work environment and compensation. These problems affect employee performance which can be seen from the decline of performance appraisal results in 2013 and 2014 of Hotel Patra Jasa Semarang as much as 5 departments.The purpose of this research is to determine the effect of organizational culture, work environment and compensation to employee performance. The type of this research is an explanatory research, the sample collecting technique is purposive sampling technique and 110 samples as respondents with data collection technique using questionnaires and interviews. This research used simple linear regression, multiple linear regression, correlation analysis, t and f test, which is supported by SPSS 16.0The result of statistical research shows that organizational culture variable, work environment and compensation have positive influence to the employee performance of Hotel Patra Jasa Semarang. The employee perceptions of organizational culture variables are very good, work environment variables are quite adequate and the compensation variable is very good, then the employee performance variable is quite good.Based on the result of the research, the researcher suggested Hotel Patra Jasa Semarang to always maintain the organizational culture, improve and maintain the quality of work facilities that was available, develop and maintain the compensation system in Hotel Patra Jasa Semarang.